From Political Economy to Economics : Method, the Social and the Historical in the Evolution of Economic Theory. - Milonakis, Dimitris (Economics as Social Theory, 30., 2008)
Developments within economics of incorporating the historical (and the social, institutional, etc more generally) have been welcomed as progress over excessive formalism and lack of realism. But, by situating these developments in terms of the shifting relationship between economics, the historical and an evolving economics imperialism, a fuller understanding of the role of economic theory and the historical is presented as a prerequisite for analysis that aspires fully to address economic and historical change.